Effect of the Planting Dates and Cutting Portions of the Shoots on Sprouting and Growth Behaviour of Populus deltoides Clones - Das, D.K.; Chaturvedi, O.P.; Chakraborty, A.K.; AIi, M.S. (Indian Journal of Agroforestry, 2020)
A nursery experiment was conducted at Pusa to find out the best planting period for the cuttings of G3 and G48 clones of Poplar (Populus deltoides) in calciorthent of north Bihar. The experiment was initiated on 15th November, 93 and planting of cuttings of length of 22 cm obtained from one-year-old shoots of poplar was repeated after one week interval up to 14th March, 94. Each shoot was divided into top, middle and bottom portions. There was a decline trend of sprouting of G3 clone planted between November 15 and November 29 and then increased gradually up to December. In between Jan. 3 and Feb. 21, bottom and middle cuttings showed 90 to 100% and 60 to 100% sprouting in G3 and G48 clones of poplar, respectively. The height and collar diameters of G3 clone after 18 months varied from 2.05 to 6.32 m and 1.45 to 6.06 cm, respectively. On the other hand, the height and collar diameter of G48 clone varied from 1.42 to 4.94 m and 1.01 to 4.01 cm, respectively. This study infers that to obtain the optimum sprouting and excellent growth of seedlings of G3 and G48 clones, the cuttings made from the bottom or middle portion of one-year-old seedling should be planted between early February to middle of March.